(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis analyzes the role of media monitoring systems in the ecosystem of modern technologies on the basis of a systematic approach. In the context of digital transformation, the increasing volume, speed and complexity of information flows are turning media monitoring programs from a simple control tool into a strategic management instrument. The study substantiates a three-level model of monitoring systems: data collection infrastructure, analytical layer and strategic management level.